Common predictors of spoken and written language performance in aphasia, alexia, and agraphia - Beeson, Pélagie M.; Rising, Kindle; Sachs, Alyssa; Rapcsak, Steven Z. (Frontiers in Human Neuroscience, 2022)
Language performance requires support from central cognitive/linguistic abilities as well as the more peripheral sensorimotor skills to plan and implement spoken and written communication. Both output modalities are vulnerable to impairment following damage to the language-dominant hemisphere, but much of the research to date has focused exclusively on spoken language. In this study we aimed to examine an integrated model of language processing that includes the common cognitive processes that support spoken and written language, as well as modality-specific skills. To do so, we evaluated spoken and written language performance from 87 individuals with acquired language impairment resulting from damage to left perisylvian cortical regions that collectively constitute the dorsal language pathway. Comprehensive behavioral assessment served to characterize the status of central and peripheral components of language processing in relation to neurotypical controls (n = 38). Performance data entered into principal components analyses (with or without control scores) consistently yielded a strong five-factor solution. In line with a primary systems framework, three central cognitive factors emerged: semantics, phonology, and orthography that were distinguished from peripheral processes supporting speech production and allographic skill for handwriting. The central phonology construct reflected performance on phonological awareness and manipulation tasks and showed the greatest deficit of all the derived factors. Importantly, this phonological construct was orthogonal to the speech production factor that reflected repetition of words/nonwords. When entered into regression analyses, semantics and phonological skill were common predictors of language performance across spoken and written modalities. The speech production factor was also a strong, distinct predictor of spoken naming and oral reading, in contrast to allographic skills which only predicted written output. As expected, visual orthographic processing contributed more to written than spoken language tasks and reading/spelling performance was strongly reliant on phonological and semantic abilities. Despite the heterogeneity of this cohort regarding aphasia type and severity, the marked impairment of phonological skill was a unifying feature. These findings prompt greater attention to clinical assessment and potential treatment of underlying phonological skill in individuals with left perisylvian damage.